Effect of Legal Actions against People Who do not Pay Their Water Bills on NWSC's Performance - Asinai, Lilian; Barigayomwe, Rogers (East African Nature and Science Organization, 2025)
This study examined the impact of legal actions against customers who fail to pay water bills on the performance of the National Water and Sewerage Corporation (NWSC) in Uganda. Using a mixed-methods approach that included both qualitative and quantitative data, the research assessed the relationship between legal enforcement measures and revenue collection. The findings indicated that a significant percentage of customers (76%) do not understand the water bill payment regulatory law, contributing to revenue loss. Although 62.4% of customers believe that NWSC strictly applies the regulations to enforce payment, over 62.5% admitted that the corporation rarely takes clients to court for non-payment. Grounded in deterrence theory, the study posits that legal penalties can effectively deter non-compliance, enhancing financial sustainability. It highlights the importance of a strong legal framework to ensure timely payments, particularly in the context of increasing urbanization that strains resources. Recommendations include implementing comprehensive awareness programs about billing regulations and strengthening legal processes for debt recovery. The insights from this research aim to improve financial performance and ensure sustainable water service delivery in Uganda